Oxy-fuel combustion boiler for CO2 capturing: 50 kW-class model test and numerical simulation - Ahn, Joon; Kim, Hyouck Ju; Choi, Kyu Sung (Journal of mechanical science and technology, 2010)
A novel oxy-fuel burner was devised and integrated into a 50 kW-class furnace-type boiler system. A series of experiments was conducted to verify its feasibility for industrial applications. Additionally, numerical simulations were performed and the results validated against experimental data on the detailed physics inside the conventional-design combustion chamber. The oxy-fuel burner, with the help of gas radiation, could effectively heat the combustion chamber. The composition of the exhaust gas revealed that the sealing of the system is crucial to the achievement of high CO 2 concentrations and low NOx emissions.